Settlement of Breach of Contract in Boarding Room Lease Agreements - Prahastika, Evira Maya; Wisnuwardhani, Diah Aju; Ariyanti, Ariyanti (Jurnal Cakrawala Hukum, 2025)
Leasing is a process in which the owner lends goods to another person in exchange for compensation, while the party using the goods must pay rent. Problems in lease agreements often arise when one party fails to fulfill its obligations according to the agreed-upon contract. Failure to fulfill these obligations can be caused by negligence, intent, or events beyond the control of each party. In Tlogomas Village, Malang City, there is a problem with the boarding house rental agreement, specifically the tenant’s default, including delays and non-compliance with payment. This study employs an empirical legal method, utilizing interviews, observations, and documentation with 121 respondents, including village employees, boarding house owners and tenants. The results of the study indicate that there are two forms of rental agreements, oral and written, but boarding house owners prefer oral agreements. When a default occurs, the owner usually gives a warning to the tenant. Oral agreements are more susceptible to default, often due to the tenant’s negligence.